Need analysis of solid geometry material learning media with character strengthening for 5th grade elementary school - Anggit Kurnia Sejati; Yuniawatika Yuniawatika; Sutansi Sutansi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
In addition to existing textbooks, student learning activities can be helped by the development of learning media that are expected to help overcome students learning difficulties, especially in math learning. This research aims to analyze the need for media that can be used in the process of learning mathematics to facilitate the understanding of materials by students. The subjects in this study were a teacher and all grade 5th students of SDN 2 Mojorembun, 16 students. Interview and questionnaire techniques are used to obtain and collect data about the learning media needs. The study results obtained an average percentage of 82.1%, which showed a need for continuous development of the need for more practical, engaging, complete learning media for solid figure material with character strengthening. So, it can be concluded that students need to develop learning media about solid figure material with character strengthening.